Real-World Evidence for the Safety and Efficacy of CGRP Monoclonal Antibody Therapy Added to OnabotulinumtoxinA Treatment for Migraine Prevention in Adult Patients With Chronic Migraine - Mechtler, Laszlo; Saikali, Nicolas; McVige, Jennifer; Hughes, Olivia; Traut, Alexandra; Adams, Aubrey Manack (Frontiers in Neurology, 2022)
Background: OnabotulinumtoxinA and calcitonin gene-related peptide (CGRP) monoclonal antibodies (mAbs) target different migraine pathways, therefore, combination treatment may provide additional effectiveness for the preventive treatment of chronic migraine (CM). Methods: Retrospective, longitudinal study using data extracted from electronic medical records (EMR) of adult patients (≥ 18 years) with CM treated with ≥ 2 consecutive cycles of onabotulinumtoxinA before ≥ 1 month of continuous onabotulinumtoxinA and CGRP mAb combination treatment. Safety was evaluated by the rate of adverse events (AE) and serious AEs. The proportion of patients who discontinued treatment and the reason(s) for discontinuation were collected. Effectiveness was assessed by reduction in monthly headache days (MHD). Outcome data were extracted from EMR at the first CGRP mAb prescription (index) and up to 4 assessments 3, 6, 9, and 12 months post-index. Results: EMR were collected for 192 patients, 148 met eligibility criteria and were included for analysis. Erenumab was prescribed to 56.7% of patients, fremanezumab to 42.6%, and galcanezumab to 0.7%. After real-world addition of a CGRP mAb to onabotulinumtoxinA, there were significant reductions in MHD at the first assessment ( 3 months) (mean -2.6 days/month, 95% CI -3.7, -1.4) and at all subsequent visits. After 12 months of continuous combination treatment, MHD were reduced by 4.6 days/month (95% CI –6.7, -2.5) and 34.9% of patients achieved ≥ 50% MHD reduction from index. AEs were reported by 18 patients (12.2%), the most common being constipation (n = 8, 5.4%) and injection site reactions (n = 5, 3.4%). No SAEs were reported. Overall, 90 patients (60.8%) discontinued one or both treatments. The most common reason for discontinuing either treatment was lack of insurance coverage (40%); few (approximately14%) patients discontinued a CGRP mAb and none discontinued onabotulinumtoxinA due to safety/tolerability. Conclusions: In this real-world study, onabotulinumtoxinA was effective at reducing MHD and the addition of a CGRP mAb was safe, well-tolerated and associated with incremental and clinically meaningful reductions in MHD for those who stayed on the combination treatment. No new safety signals were identified. Of those who discontinued, the majority reported lack of insurance coverage as a reason.